2019
DOI: 10.1371/journal.pone.0221964
|View full text |Cite
|
Sign up to set email alerts
|

Association of antibiotic exposure with the mortality in metastatic colorectal cancer patients treated with bevacizumab-containing chemotherapy: A hospital-based retrospective cohort study

Abstract: BackgroundPreclinical studies showed that antibiotic exposure played a role in clinical outcomes in patients with chemotherapy via modulation of microbiota. However, it remains unknown whether antibiotic exposure during the bevacizumab therapy affects the clinical outcomes in metastatic colorectal cancer(mCRC) patients. This study aimed to examine the association between the antibiotic medication and the clinical outcomes in mCRC patients with bevacizumab therapy.MethodsThis retrospective cohort analysis inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…However, this very artificial system also demonstrates the importance of the microbiota in protecting the host as even STm ∆aroA could invade and infect systemically. Treating cancer patients with antibiotics prior to surgery is common practice, however in light of the importance of diverse microbiota for controlling cancer (28,29) it has become apparent it is not optimal for patient outcome, with anti-biotic preconditioning leading to worse outcomes (57)(58)(59). Our data do not exclude that there could be certain microbiota compositions that will enable more effective therapy, as with checkpoint blockade therapy (28,29,59), and thus analyzing microbiomes may be something to consider when starting human clinical trials with orally delivery BCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, this very artificial system also demonstrates the importance of the microbiota in protecting the host as even STm ∆aroA could invade and infect systemically. Treating cancer patients with antibiotics prior to surgery is common practice, however in light of the importance of diverse microbiota for controlling cancer (28,29) it has become apparent it is not optimal for patient outcome, with anti-biotic preconditioning leading to worse outcomes (57)(58)(59). Our data do not exclude that there could be certain microbiota compositions that will enable more effective therapy, as with checkpoint blockade therapy (28,29,59), and thus analyzing microbiomes may be something to consider when starting human clinical trials with orally delivery BCT.…”
Section: Discussionmentioning
confidence: 99%
“…477,478 Antibiotic use, which might dramatically reduce gut microbial diversity and density, was found to be related to poor survival in patients with metastatic CRC who had received bevacizumab therapy. 479 However, the influence of the microbiota on anti-VEGF agents is still a matter of debate because of the controversial reported results 480,481 in renal cell cancer-based studies stating an unclear role of antibiotics in VEGF-blockade therapy.…”
Section: Immune Checkpoint Inhibitor Therapymentioning
confidence: 99%
“…A retrospective study showed that patient outcomes can be improved during immunotherapy with bevacizumab using antibiotics. Patients with metastatic colorectal carcinoma had lower mortality rates if treated with antibiotics for a more extended period [36]. Another study showed that Fusobacterium nucleatum was abundant in colorectal-carcinoma patients with recurrence after chemotherapy.…”
Section: Complications During Chemo-and Immunotherapymentioning
confidence: 99%